Adaptive Reflection on Negative Emotional Experiences: Convergences and Divergence Between the Processing-Mode Theory and the Theory of Self-Distancing Reflection - Cova, Félix; Garcia, Felipe; Oyanadel, Cristian; Villagran, Loreto; Páez, Dario; Inostroza, Carolina (Frontiers in Psychology, 2019)
Reflecting on negative emotional experiences can be adaptive but it can also maintain or intensify detrimental emotional states. Which factors determine whether reflection can have one consequence or another is unclear. This study focused on two research programs that have concentrated on this topic in the last decades: processing-mode theory (PMT) and self-distancing theory (SDT). The article described and contrasted both programs and their findings. The promising results that PMT and SDT have achieved in identifying the differences between the forms of adaptive and maladaptive reflection are highlighted. Likewise, the disconcerting contradictions observed between both programs that make integrating the findings difficult are indicated. The PMT states that adaptive reflection is concrete, and it is focused on the how of the experience. The SDT states that adaptive reflection is self-distanced and focused on the global meaning of the experience. The article finishes by indicating possible explanations for these apparent contradictions and outlines the challenges to be solved to improve comprehension of the topic.